Letters for a Nation : From Jawaharlal Nehru to his Chief Ministers 1947-1963 - Jawaharlal Nehru (Penguin Books India, 2015)
In October 1947, two months after he became independent India's first prime minister, Jawaharlal Nehru wrote the first of his fortnightly letters to the heads of the country's provincial governments--a tradition he kept until a few months before his death. This carefully selected collection covers a range of themes and subjects, including citizenship, war and peace, law and order, governance and corruption, and India's place in the world. The letters also cover momentous world events and the many crises the country faced during the first sixteen years after Independence. Visionary, wise and reflective, these letters are of great contemporary relevance for the guidance they provide for our current problems and predicaments.